SUSY Searches at ATLAS - Jong Paul de (EPJ Web of Conferences, 2012)
Recent results of searches for supersymmetry by the ATLAS collaboration in up to 2 fb−1 of √s = 7 TeV pp collisions at the LHC are reported.